(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2020)
The present study aimed to develop the new method for the estimation and validation of tenofovir in pure form and in pharmaceutical dosage form by RP-HPLC. The chromatogram of tenofovir was developed through column (Hyper ODS2 C18), UV detection at 260 nm at a flow rate of 1.2 ml/min with Methanol and Phosphate buffer (90:10) as mobile phase. The method was validated by various validation parameters such as accuracy, precision, linearity, specificity as per the ICH guidelines. A linearity range and retention time of Tenofovir were found to be 20-110 µg/ml and 2.1 min respectively. The % RSD of the Tenofovir was found to be 0.7. The % recovery was obtained as 99.7% for standard and 96.32% for tablets. This method was simple, accurate, precise and sensitive. Hence, the developed method was employed for the routine analysis of Tenofovir in the pharmaceutical dosage form.